Analisis Efektivitas Fitoremediasi Berbasis Tanaman Hias pada Konsentrasi Formaldehida Dalam Ruangan untuk Meningkatkan Health and Safety Pekerja - Inas, Bilqis Hanifah; Dewi, Ratna Sari (Rekayasa, 2025)
Indoor air quality is a crucial factor that directly impacts worker safety and health (K3), where exposure to hazardous pollutants such as formaldehyde can trigger irritation, respiratory disorders, and long-term health risks. Based on this issue, this study aims to analyze in depth the effectiveness of a phytoremediation strategy using ornamental plants in reducing formaldehyde concentrations in office workspace environments. To achieve this goal, sophisticated simulations were conducted using Computational Fluid Dynamics (CFD) methods through the SimScale platform. Four main intervention scenarios were modeled in detail: (1) a control condition with no intervention, (2) the use of mechanical ventilation alone, (3) ornamental plant intervention alone, and (4) a synergistic combination of ventilation and plants. In this simulation, formaldehyde emissions were assumed to originate from the work desk material, while the ornamental plant Ficus benjamina acted as a passive absorbing agent. The simulation results showed that the combination of ventilation and plants was the most superior strategy, capable of drastically reducing formaldehyde concentrations by up to 99.8% in just one hour. Meanwhile, plant intervention alone also made a significant contribution with a reduction of 46%. Further statistical analysis using multiple linear regression and ANOVA confirmed that all interventions had highly significant effects (p 0.05). Furthermore, it was revealed that plant placement influenced absorption effectiveness, with positions closer to the emission source showing better absorption. These findings emphasize the importance of an integrated strategy between plant arrangement and ventilation engineering to create a healthy, safe, and productive work environment.